Some Features of the Bacteria of the Family Enterobacteriaceae Allocated from Small Cattle at Different Pathological Processes - Ruslan Gayrabekov1, Raisa Gayrabekova1, Luiza Molochaeva1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Enterobacteria with a certain set of pathogenicity factors and capable of leading to the development of diseasesof animals and humans are ubiquitous in nature, which can be recognized as the result of anthropogenicactivity. Recently, they have been isolated with increasing frequency from soil, water, from fruits,vegetables, grains, plants, from representatives of various systematic groups of animals and humans. Wehave obtained bacteria from sheep with gastrointestinal pathologies. From sick animals, we have identified alarge number of bacterial cultures belonging to species of different genera of the Enterobacteriaceae family.Among them, 190 cultures, species belonging to Escherichia coli, 124 cultures of Enterobacter cloacae,74 cultures of Morganella morganii, 51 culture of Citrobacter freundii, 29 cultures of Serratia marcescens.For these microorganisms a large set of various pathogenicity factors was characteristic: antilysocyme,anti-complementary, anti-interferon activity, adhesive ability, hemolytic activity, multiple resistance toantibacterial drugs.The aim of our work is to study the spread of enterobacteriosis, some features of the epizootic process inthese diseases in the territory of the Chechen Republic